EFFICACY OF INTRAVESICAL INSTILLATION OF NETILMICIN ON MANAGING UTI - Praba, Barry Arief; Utomo, Trisula (Indonesian Urological Association, 2015)
INTRODUCTION Urinary tract infections (UTIs) are common, affect men and women of all ages, and vary dramatically in their presentation and sequelae. They are a common cause of morbidity and can lead to significant mortality. New antimicrobial agents that achieve high urinary and tissue levels, that can be administered orally, and that are not nephrotoxic have significantly reduced the need for hospitalization for severe infection. Shorter-course therapy and prophylactic antimicrobial agents have reduced the morbidity and cost associated with recurrent cystitis in women. Intravesical instillation of aminoglycoside has been used empirically as prophylaxis and to treat bacilluria in spinal-cord-injured patients undergoing clean intermittent catheterization.METHODS In a prospective clinical trial performed in the urologic ward of Dr. Sardjito Hospital, yogyakarta, Indonesia, we studied 56 patients who has indwelling urethral catheter more than 4 days. Patients were divided into two groups. In group 1 (28 patients) one-time intravesical instillation of Netilmicin 25 mg was administred, and in group 2 (28 patients) none were given any treatment. Urinalysis was evaluated before and after instillation of Netilmicin. Statistical data and results were studied using descriptive statistics as median (minimum and maximum). To compare the response to treatment, Chi-Square test was used in two groups. Consequently, the data were analyzed using the SPSS 17 software.RESULTS Urinalysis were evaluated in two groups 4 days after intravesical instillation of 50 mg netilmicin. The patients we studied, the median age 59 years old (min. 29; max. 81). In the first group we found 22 (78,5 %) patients still without UTI, 6 (21,5 %) patients with UTI, in the second group we found 4 (14,3 %) still without UTI, 24 (85,7 %) patients with UTI. The difference was statistically significant (p=0.0001)CONCLUSIONS Intravesical instillation of netilmicin on patients with indwelliing urethral catheter were effective on preventing catheter-related UTI.Keywords : UTI, indwelling catheter, netilmicin, intravesical antibiotic instillation.